Preserving Balinese Folklore: The Development of 'The Origins of Buleleng and Singaraja' via Augmented Reality - I Ketut Yudi Premana Giri; I Gede Mahendra Darmawiguna; Ida Bagus Nyoman Pascima (IJNMT (International Journal of New Media Technology), 2026)
This study presents the development and validation of an Augmented Reality (AR) application centered on the Balinese folklore "The Origins of Buleleng and Singaraja." Utilizing the Multimedia Development Life Cycle (MDLC) model, which includes six stages”concept, design, material collection, assembly, testing, and distribution”the research aims to enhance public engagement, awareness, and understanding of Balinese cultural heritage. The application underwent rigorous testing, including expert content validation, media expert assessment, and user response evaluation. The content and media tests, analyzed using Gregory's formula, yielded a perfect validity score of 1.00, indicating a "very high" level of accuracy and effectiveness in both historical narrative presentation and AR content delivery. User feedback, collected from 35 respondents, showed a 97.30% response rate in the "very positive" and "very good" categories, with the remaining 2.70% in the "good" category. These results demonstrate strong user approval and the potential of AR technology to preserve and promote Balinese folklore.